IFITM3 enhances immunosensitivity via MHC-I regulation and is associated with the efficacy of anti-PD-1/-L1 therapy in SCLC - Yanan Cui; Tianyu Qiu; Jiale Wang; Xinyu Liu; Libo Luo; Jizhong Yin; Xinxin Zhi; Wanying Wang; Gaohua Feng; Chunyan Wu; Zhikai Zhao; Hua Zhang; et al. (Molecular Cancer)
Abstract Background Most small cell lung cancer (SCLC) patients exhibit resistance to immune checkpoint inhibitors (ICIs) and demonstrate downregulation of major histocompatibility complex class I (MHC-I) molecules. This study aimed to elucidate the regulatory mechanisms underlying MHC-I expression and potential combination strategies. Methods Single-cell and bulk RNA sequencing data from SCLC patients were analyzed. Clinical data from SCLC patients treated with PD-1/PD-L1 inhibitors were used to investigate the associations between treatment efficacy and IFITM3 expression. In vitro and in vivo functional studies were conducted to evaluate the role and mechanisms of IFITM3 in modulating tumor sensitivity to PD-1 inhibitors. Results Integrative analysis of multiple real-world SCLC cohorts confirmed a significant positive association between IFITM3 expression and MHCI. IFITM3 overexpression upregulated MHC-I-related genes, enriched antigen presentation pathways, and increased CD8+ T-cell infiltration and cytotoxicity. Elevated IFITM3 expression was significantly associated with prolonged progression-free survival (PFS) in patients receiving chemoimmunotherapy but not in those treated with chemotherapy alone. Additionally, patients with high H-scores for IFITM3, as determined by immunohistochemistry, demonstrated better clinical outcomes with chemoimmunotherapy. Inducing IFITM3 expression directly or through treatment with ethyl gallate (EG), an IFITM3 inducer, effectively sensitized tumors to PD-1 blockade in SCLC mouse models. Mechanistic studies revealed that IFITM3 upregulates NLRC5, a key transcriptional activator of MHC-I, facilitating its nuclear translocation and thereby increasing MHC-I levels. Conclusions IFITM3 is associated with MHC-I expression and can predict the efficacy of anti-PD-1/-L1 therapy in SCLC patients. IFITM3 inducers potently improved the efficacy of anti-PD1 monotherapy in SCLC.